SUCCESSFUL TRANSURETHRAL RESECTION OF ANTERIOR URETHRAL VALVE IN CHILDREN : A CASE REPORT - Akbar, Fariz Kemal; Seputra, Kurnia Penta; Nurhadi, Pradana (Indonesian Journal of Urology, 2024)
Objective: This case report will present transurethral resection of double anterior urethral valves in tertiary hospital. Case(s) Presentation: A three-year-old boy who complained of a poor stream of urine and discomfort during micturition. From the radiological examination, the main finding was found on ultrasound (USG), with thickening of the bladder wall without upper tract abnormality. On panendoscopy, we found double anterior urethral valves at bulbar part and trabeculation in bladder. Discussion: The resection of the valves was performed and achieved an excellent result included normal stream of urine and there was no discomfort during micturition. Conclusion: Anterior Urethral Valve is a rare case that can be caused a lower urinary tract obstruction. A good understanding of AUV’s radiological and endoscopic anatomy is required to differentiate it from other diseases, essential to prevent further injury, and also to decide for appropriate management. Keywords: Anterior Urethral Valve, Congenital Anomaly, Urinary Obstruction